TANTANGAN DI ERA INDUSTRI 4.0: PENGARUH INTENSITAS TAYANGAN PROGRAM TELEVISI TERHADAP PENGGUNAAN BAHASA INDONESIA - Eka Septiani; Nur Indah Sari; Sri Mulyani (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2019)
Television media is one of the challenges we are currently facing  in era 4.0. The challenge that we face through television media are, among other things,how we can choose educational television programs, especially those that still prioritize the use of Indonesian language that is good and correct in its presentation. Ironically, most television programs presented no longer heed the standard Indonesian language. This study aims to find out how teenagers in this case are students can view and choose television programs that they watch every day. Based on these objectives, researchers used descriptive analysis methods through questionnaires. The selected sample was taken as many as 30 student randomly. From the result of the analysts, the data shows that television programs are currently very influential in facing challenge in era 4.0 againts the standard use of Indonesian among teenagers. Today’s television programs are lacking especially in terms of language in the screening so that it becomes a challenge for teenagers so that they are able to maintain the use of goog and correct Indonesian. Keyword: television programs, the challenge of era 4.0, Indonesian language shift.